Smart Trash Klasifikasi Sampah Otomatis Dengan Sensor Proximity Berbasis Arduino - Muhammad Anas; Nuzul Hikmah; Ira Aprilia (Jurnal FORTECH, 2022)
Garbage is still a serious problem in Indonesia. Because, the impact can not only damage the environment, but also threaten human health. Garbage is divided into 3 types, namely organic, inorganic and metal which can be decomposed or not biodegradable and is considered no longer useful so that it is disposed of in the environment. Garbage sorting is usually done manually by a janitor before the waste is disposed of to the TPA for re-sorting. The purpose of waste sorting is to facilitate further waste management. This study uses a flowchart to assist the process of analysis and problem solving in research. Flow chart (Flowchart) is a graphical picture consisting of symbols. the results of the research in making a tool in the form of Smart Trash Automatic Garbage classification with Arduino Based Proximity Sensors are. This tool is made to facilitate automatic waste sorting. People who want to dispose of trash no longer have to open and close the lid of the trash can because the lid of the trash can open and close automatically.The working system of this automatic waste classification tool is that when waste is made of organic, inorganic and metal materials, it will be classified automatically into the trash bins that have been prepared. The waste sorting system 2 can only accommodate a maximum waste weight of 100 grams and the waste sorting place 1 is at least 6 grams.